Inpatient COVID‐19 outcomes in solid organ transplant recipients compared to non‐solid organ transplant patients: A retrospective cohort. Issue 7 (21st February 2021) - Avery, Robin K.; Chiang, Teresa Po‐Yu; Marr, Kieren A.; Brennan, Daniel C.; Sait, Afrah S.; Garibaldi, Brian T.; Shah, Pali; Ostrander, Darin; Steinke, Seema Mehta; Permpalung, Nitipong; Cochran, Willa; Makary, Martin A.; et al.
Abstract : Immunosuppression and comorbidities might place solid organ transplant (SOT) recipients at higher risk from COVID‐19, as suggested by recent case series. We compared 45 SOT vs. 2427 non‐SOT patients who were admitted with COVID‐19 to our health‐care system (March 1, 2020 ‐ August 21, 2020), evaluating hospital length‐of‐stay and inpatient mortality using competing‐risks regression. We compared trajectories of WHO COVID‐19 severity scale using mixed‐effects ordinal logistic regression, adjusting for severity score at admission. SOT and non‐SOT patients had comparable age, sex, and race, but SOT recipients were more likely to have diabetes (60% vs. 34%, p < .001), hypertension (69% vs. 44%, p = .001), HIV (7% vs. 1.4%, p = .024), and peripheral vascular disorders (19% vs. 8%, p = .018). There were no statistically significant differences between SOT and non‐SOT in maximum illness severity score ( p = .13), length‐of‐stay (sHR: 0.9 1.11.4, p = .5), or mortality (sHR: 0.1 0.41.6, p = .19), although the severity score on admission was slightly lower for SOT (median [IQR] 3 [3, 4]) than for non‐SOT (median [IQR] 4 [3–4]) ( p = .042) Despite a higher risk profile, SOT recipients had a faster decline in disease severity over time (OR = 0.76 0.810.86, p < .001) compared with non‐SOT patients. These findings have implications for transplant decision‐making during the COVID‐19 pandemic, and insights about the impact of SARS‐CoV‐2 on immunosuppressed patients. Abstract : This comparison of inpatient transplant and nontransplant recipients with COVID‐19 does not show differences in mortality or measures of illness severity but does show that time to improvement was more rapid in the transplant group.